Professional's Calling: Mental Healthcare Staff's Attitudes to Spiritual Care - Parkes, Madeleine (Implicit religion, 2011)
Mental health professionals enter the service with a desire to work to provide better outcomes for service users and carers. However sometimes the system gets in the way and produces unintended consequences. Recently service users have requested that the spiritual dimension of their lives be given greater attention, and this fits strongly with the recovery approach and its accent on service users being able to take control of their own lives. Research undertaken at Birmingham and Solihull Mental Health Foundation Trust has found that staff across all professional groups have recognized the importance of spirituality and spiritual care and wish to receive greater guidance and education in how to respond to services user needs